Karya Tabuh Kreasi “Pitu” - I Putu Hare Krsna Darma Yoga (Institut Seni Indonesia Denpasar, 2023)
Purpose: the number seven is a mysterious, unique, magical and meaningful number. Hindu Religion, the number seven is believed to have a special feature because there are seven layers on Earth, namely patala. Methods: the process of creating Pitu's work is an attempt to create a new work of art, especially in the field of Balinese Karawitan art. Pitu's work is a musical creation that uses three parts including, part I (kawitan), part II (gegenderan and bapang), part III (cutter and pekaad). The stylist creates a creation percussion which is structurally starting from kawitan to pekaad which is based on the number seven. The media used in Tabuh Kreasi Pitu uses the gamelan Semar Pegulungan Saih Pitu with a seven-tone pelog barrel to be used as a medium for saying. Pitu's creation of tabuh uses several counts of seven which are combined with dynamics, tempo and melodic games that are developed so as not to look monotonous. Result and discussion: as an academic artist who has more abilities in the academic field, he should be able to create a quality and weighty work. Implication: It is hoped that Tabuh Kreasi Pitu can provide more space for students to be creative by organizing compositional events outside class hours.